2021
DOI: 10.3390/min11080892
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hydrothermal Precipitation of Alunite and Natroalunite in High-Aluminum Vanadium-Bearing Aqueous System

Abstract: During the acid leaching process of black shale, with the destruction of the aluminosilicate mineral structure, a large amount of aluminum (Al) is leached, accompanied by the release of vanadium (V). To separate aluminum from the vanadium-containing solution, the precipitation behavior of aluminum ions (Al3+) was investigated under hydrothermal conditions with the formation of alunite and natroalunite. In the solution environment, alunite and natroalunite are able to form stably by the Al3+ hydrolysis precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There are two exceptions: the first is the formation of antlerite, equation (30), and this is consistent with the study of Yoder et al [113] who reported that this phase cannot be formed at room temperature from reactions between 0.05-1.2 M CuSO 4 and 0.05-1.0 M NaOH solutions. The second is the formation of natroalunite, Equation (28) which typically employs temperatures above 100 • C for synthesis (e.g., [152]).…”
Section: Chemical Thermodynamicsmentioning
confidence: 99%
“…There are two exceptions: the first is the formation of antlerite, equation (30), and this is consistent with the study of Yoder et al [113] who reported that this phase cannot be formed at room temperature from reactions between 0.05-1.2 M CuSO 4 and 0.05-1.0 M NaOH solutions. The second is the formation of natroalunite, Equation (28) which typically employs temperatures above 100 • C for synthesis (e.g., [152]).…”
Section: Chemical Thermodynamicsmentioning
confidence: 99%
“…Ad sorp tion phe nom ena are also im por tant, e.g., for Al, Cd, Cu and Zn, as shown by the computer sim u la tions of Hud son-Ed wards and Wright (2011). The ad sorp tion is pos si ble due to the neg a tive charge of the ASM sur face (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alum mines are distinguished from metal and coal mines by the production of waste slag containing alunite (KAl(SO₄)₂·12H₂O) [ 32 ]. The ionization of alunite can further aggravate the degree of water acidification caused by pyrite [ 33 ]. In the past, alum mining activities produced large amounts of waste slag, some of which comprised low-grade ores discarded from open-pit mining, which accumulated on many parts of the surface without any anti-pollution measures.…”
Section: Introductionmentioning
confidence: 99%